Application for 20% of the L/C price of eighth & ninth batch steel members - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the application for 20% of the L/C price of the eighth & ninth batch batch steel members for BRACU new campus project.